Web Server Load Balance Design In Internet Network Using Nth Method - Rahmat Kurniawan; Herlina Latipa Sari; Hari Aspriyono (Jurnal Media Computer Science, 2023)
This study aims to build a load balance web server using the NTH load balance method, apply a balanced distribution of connection paths to the two web servers, and reduce the traffic load on the connection path and also the web server. This study uses the action research method, which uses this method to describe, interpret and explain a condition at the same time as carrying out interventions aimed at improvement or participation. The results of this study indicate that web server load balance can be carried out using the NTH method which is applied to proxy routers. The application of the NTH method can divide the connection path between the two servers in a balanced manner and can reduce the traffic load on each predetermined connection path. In addition to applying load balance, data replication in the database can also be done as well as synchronizing files in the web application directory..